Menemukan Ikigai: Merancang Masa Depan Dengan Passion Dan Potensi - Hasanah, Yulia Nur; Suprayogi, Yogi; Rizaldi, Fikri Mohamad (Cahaya Pengabdian, 2025)
This community service program aims to help Darul Hikam High School students in finding Ikigai, a Japanese concept which means "reasons for life," as a basis for designing a future that is in harmony with their passion and self-potential. Through a series of educational activities in the form of workshops, discussions, and independent reflections, participants are invited to understand themselves, explore interest and talent, and connect internal motivation with realistic and satisfying career goals. Evaluation is done by measuring participants' satisfaction with the material, implementation, and services during the activity. The results show a very high level of satisfaction, indicating the success of the program in providing understanding and motivation that strengthens the readiness of students to meet the future. In conclusion, the IKIGAI approach is effective as a method of self -development of adolescents in the context of education and community service.